PENGARUH PENAGIHAN PAJAK, KUALITAS PENETAPAN PAJAK, DAN KEPATUHAN WAJIB PAJAK TERHADAP PENCAIRAN TUNGGAKAN PAJAK (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Semarang Timur) (Students' Journal of Accounting and Banking, 2014)
This research purpose to analyze the factors that affect the disbursement of tax arreaars. The variables used in this study are tax collection, tax assessment quality, and tax compliance by taking the object of research in KPP Pratama Semarang Timur. The research method used is a quantitative method using secondary data. The study involved a sample as many corporate taxpayers and individual taxpayers who have tax arrears during the period 2010-2012. Analysis of the data using a normality test, multicollinearity, heteroscedasticity test, autocorrelation test, multiple linear regression, R2 test, F test, and T test. Data calculations performed using SPSS version 19.0 for windows. The results showed that the tax collection with a reprimand letter and force letter no positive effect on corporate disbursement tax. The tax collection with a reprimand letter give positive effect while force letter no positive effect on individual disbursement tax. Tax assessment quality give no positive effect on corporate and individual disbursement tax. Tax compliance give possitive effect on corporate and individual disbursement tax.Keywords: tax collection, tax assessment quality, tax compliance, disbursement of tax